The Elicit Function of Speech Acts in Questioning on Investigative Interviews in Criminal Inspection of Dump Truck Theft Cases at Cirebon City Police Station - Andika Dutha Bachari (Universitas Pasundan, 2022)
In this study, the data source was obtained from the transcription of dump truck theft cases recorded in the Police Record. Investigators conducted investigative interviews to obtain information from witnesses and suspects, which led to the suspect's confession. The investigator asked several questions to the examinee regarding the criminal act. The data analysis method was carried out by eliminating the answers being examined and focusing on the questions given by the investigator to be classified based on the seven elicit functions of the speech act of asking questions described by Tsui (2002). It was found that the elicit function in the investigator's question was the function of seeking information (appearing 119 times), repeat function (appear 50 times), clarifying function (appear 47 times), confirm function (appear 43 times), and approve function (appear 11 times). The elicit function that occurred the most from the questions submitted by investigators was the function of seeking information, which was 119 times out of 270 questions. In contrast, the function of asking for commitment was not found. Keywords: ask, elicit function, investigative interview speech act